Answer :

Formula used.


(a – b)2 = a2 – 2ab + b2


3x2 – 5xy + 3y2


Add and subtract xy to the equation.


3x2 – 5xy + 3y2 [ + xy – xy]


3x2 – 6xy + 3y2 + xy


3[x2 – 2xy + y2] + xy


3[x-y]2 + xy


x = 2 + √3


y = 2 – √3


xy = (2 + √3) × ( 2-√3)


xy = (2)2 – (√3)2


= 4 – 3


= 1


x – y = 2 + √3 – [2-√3]


x – y = 2√3


Putting the values we get;


3[2√3]2 + 1


3[12] + 1


36 + 1 = 37


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

In each of the foWest Bengal Board - Mathematics

If <span lang="ENWest Bengal Board - Mathematics

If we subtract <sWest Bengal Board - Mathematics

Let us write a raWest Bengal Board - Mathematics

Let us rationalizWest Bengal Board - Mathematics

Let us write the West Bengal Board - Mathematics

Let us write whetWest Bengal Board - Mathematics

Let us fill up thWest Bengal Board - Mathematics

Let us divide firWest Bengal Board - Mathematics

The product of <sWest Bengal Board - Mathematics